Faktor-faktor yang Memengaruhi Organisasi Dalam Mengadopsi Teknologi Blockchain di BPJS Ketenagakerjaan: Factors Affecting The Adoption of Blockchain Technology in Organization on BPJS Ketenagakerjaan - Thahir, Abizar Giffari; Hubeis, Musa; Sukmawati, Anggraini (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The acceleration of digital transformation in organizations plays a critical role in supporting business processes and selecting appropriate technologies to address organizational challenges and issues. Currently, blockchain technology has garnered significant attention among practitioners and academics due to its versatile applications. This study aims to analyze the factors influencing the adoption of blockchain technology at BPJS Ketenagakerjaan using the technology-organization-environment (TOE) framework model to map the determinants of blockchain technology adoption. The analysis is conducted through a structural equation modelling (SEM) approach. The research results from 150 respondents indicate that technology, organization and environment have a significant and positive impact on the adoption of blockchain technology. However, organizational culture does not have a moderating effect on this study. Additionally, the study examines the effects of blockchain technology adoption on organizational performance. In order to successfully adopt blockchain technology, BPJS Ketenagakerjaan need to consider technological, organizational and environmental factors. Moreover, collaboration with organizations that have already adopted blockchain technology and partnerships with educational institutions to explore the full potential of this technology are recommended. Keywords: blockchain, BPJS Ketenagakerjaan, TOE Framework, organizational performance, technology